Contemporary Islamic Jurisprudence Study On Interfaith Marriage: A Review Of Modern Schools Of Thought And Scholars - Dinda Suciana Rambe; Raja Albar Pandapotan Simatupang; Manswab Mahsen Abdulrahman (AT-TAFAHUM: Journal of Law, 2021)
Interfaith marriage has become an increasingly significant issue in contemporary Islamic jurisprudence due to the growing interaction among people of different religious backgrounds in the era of globalization. While Islamic teachings provide legal guidance on marriage, contemporary scholars have sought to reinterpret classical rulings by considering the objectives of Islamic law (maqasid al-shariah) and the realities of modern pluralistic societies. This study aims to analyze the concept of interfaith marriage from the perspective of contemporary Islamic jurisprudence, examine the views of the four major Sunni schools of law and contemporary Muslim scholars, and explore its relevance within the Indonesian legal system. The research employs a qualitative approach using normative juridical and library research methods. Primary data consist of the Qur'an, Hadith, and classical as well as contemporary Islamic legal literature, while secondary data are obtained from scientific journals, books, and Indonesian marriage regulations. The collected data were analyzed descriptively and analytically to identify similarities, differences, and contemporary legal implications. The findings reveal that the four Sunni schools generally prohibit Muslim women from marrying non-Muslim men, while differing opinions exist regarding Muslim men marrying women from the People of the Book (Ahl al-Kitab). Contemporary scholars such as Yusuf al-Qaradawi and Quraish Shihab acknowledge the textual permissibility of such marriages but emphasize that they should be assessed based on public interest, family harmony, and the religious upbringing of children. In Indonesia, interfaith marriages are not legally recognized under Law Number 1 of 1974 because marriage validity depends on compliance with the respective religious laws of the parties involved. The study concludes that although contemporary Islamic jurisprudence provides room for contextual interpretation, the principles of preserving faith, family stability, and social welfare remain the primary considerations in determining the legal status of interfaith marriage.